Dimensiones y características nutritivas de las bellotas de los Quercus de la dehesa (Arch. Zootec, 2008)
Acorns production of Quercus (Q. ilex, Q. suber, etc.) is an important feeding resource in the dehesa during autumn-winter. Acorn weight, size and shape present a lot of variability between species, species, individuals and areas. Also composition is variable and is influenced by its own maturation process and external agents (humidity, parasites, etc.). Op.osite, shell and cotyledons proportions show higher homogeneity. Shell composition has a very high level of tannins and lignin, which affects its digestibility. Kernel has a very high level of glucids (80% of DM) and lipids (5-10% of DM) with a oleic acid content up.er 60%, however protein level is very low (4-6% of DM). Many wild and domestic species eat acorns; however, in the dehesa, acorns are used to feed fattening Iberian pigs because this breed is the single one capable of peeling them and rises a high commercial value